Hip-sparing approach using computer navigation in periacetabular chondrosarcoma. (January 2013) - Gerbers, J.G.; Jutte, P.C.
<x xml:space="preserve">Abstract</x> Chondrosarcoma of the pelvis is difficult to treat due to the anatomical location and the high incidence of recurrence. Treatment is primarily surgical, and the surgical margins, based on MSTS criteria, have been shown to be predictive of disease recurrence and mortality. However, too-wide margins can decrease post-operative function. In the presented case, computer assisted surgery (CAS) was used to safely enable a joint-salvaging approach in a modified type 2/3 resection of a grade 2 chondrosarcoma of the os ischium and os pubis. The CAS navigation was vital to achieving the desired safe margins. The current follow-up period is 3.5 years, and the patient is disease-free, with no local recurrences or metastases having been detected. Post-operative function is excellent, with good MSTS and SF36 scores. This outcome is a good example of the value of CAS in certain cases.